Sudden onion price surge in Bangladesh: A situation analysis for policy - Ahmed, Akhter; Kaikaus, Ahmad (University Press Limited, 2021)
Onion is a key ingredient in most Bangladeshi meals, so its sudden price spurt in the domestic market in early-July 2013 raised deep concerns among the people and the government. While such a price surge hits low-income consumers the hardest, it can also become an important political issue. For example, in India, onion prices were regarded as the decisive factor in the 1998 state elections in Delhi and Rajasthan and were responsible for bringing down the central government in 1980. Following the 2013 price hike, a situation analysis of the onion price surge was conducted with a view to derive recommendations for onion price stabilization in the country. The analysis of onion price situation was based on information collected from a number of sources.